Financing Education in the Development of the Islamic Education System - Rita Nurjanah; Hasan Basri; Nurhayati, Nurhayati; Siti Romlah (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to identify a legal basis, sources, components and challenges in the management of Islamic education financing, and offer solutions to these problems. The method used is a qualitative approach to analyze related issues and produce strategic recommendations to improve the effectiveness of Islamic values-based education programs. The results show that the legal basis of Islamic education financing is based on the National Education System Law No 20 of 2003 and Minister of National Education Regulation No 69 of 2009. The financing components include investment, operational and personal costs. Challenges in management include limited funding sources, high education costs, and lack of transparency and accountability. To overcome these issues, the researchers recommend diversifying sources of financing, improving accountability and developing a financing plan. The findings are expected to make a significant contribution to Islamic education policy in Indonesia and serve as a reference for educational institutions in designing more effective financing strategies.